Change Readiness On The Covid-19 Pandemic In Higher Education Activities: The Student Perspective - Nurillah Jamil Achmawati Novel; Rani Sukmadewi; Jovanscha Qisty Adinda Fildzah (Universitas Padjadjaran, 2022)
The COVID-19 pandemic has had both positive and negative impacts on various aspects of life, including the world of education. Social restrictions cause teaching and learning activities to be carried out from their respective workspaces, or what is known as online learning. This study identifies the changing readiness of students in higher education related to the adaptation of online learning activities. As the result of all the dimensions specified, only two dimensions are optimal, namely